Jatio Sangsad Bhaban: Aspiring to be a UNESCO World Heritage Site - Bayezid Ismail Choudhury (Journal of Social and Development Sciences, 2021)
The Jatio Sangsad Bhban (JSB) or the National Assembly Building of Bangladesh is an internationally renowned architectural masterpiece designed by eminent 20th-century American architect Louis I. Kahn. Its unique Architectural merit makes it one of the most significant buildings of the 20th century. The impact of this iconic building encompasses all spheres of Bengal life including culture, heritage, ethos and lifestyle. Its architectural values also evoke national identity, symbolizing the hopes and aspirations of the people of Bangladesh. However, despite its international and national material, social and human significance, it is yet to be nominated as a UNESCO World Heritage Site (WHS). This paper argues for the potential of the JSB to become a WHS.